Tregopathy in focus - Iyengar, Vaishnavi Venkatachari; Gowri, Vijaya; Chougule, Akshaya Sanjay; Taur, Prasad; Madkaikar, Manisha Rajan; Bodhanwala, Minnie; Desai, Mukesh Manharlal (Frontiers in Immunology, 2025)
Primary immune regulatory disorders are a newly coined term for a group of disorders in which autoimmune complications predominate. Herein, we present a case series of 26 patients with various regulatory T-cell (Treg) pathway defects who presented with multiple autoimmune complications. Twenty-six patients with pathogenic variants in T regulatory pathway genes were included, and their clinical data were evaluated. The median age at onset was 4.25 years, and the median delay in diagnosis was 2 years. The male-to-female ratio was 17:9. Thirteen children had LRBA deficiency, five had CTLA4 defect, two had IPEX, two had Cluster of differentiation 25 (CD25) defect, two had signal transducer and activator of transcription 3 (STAT3) Gain of function (GOF), and two had Fermitin family member 1 (FERMT1). Autoimmune cytopenia was the most common form of autoimmunity observed. Other autoimmune diseases included autoimmune hepatitis, inflammatory bowel disease, enteropathy, type 1 diabetes mellitus, thyroiditis, central nervous system (CNS) vasculitis, glomerulonephritis, and dermatitis. Most patients had evidence of lymphoproliferation with generalized lymphadenopathy and/or hepatosplenomegaly; 7/21 had hypogammaglobulinemia, 13/22 had low B-cell subsets, and 6/22 had low Cluster of differentiation 3 (CD3) levels. The treatments were diverse and included corticosteroids, cyclosporine, azathioprine, cyclosporine, and rituximab. After diagnosis, 12 patients were started on mTOR inhibitors, four on abatacept, and two on JAK inhibitors, with better control of autoimmunity. Five children underwent HSCT, and four are currently doing well. Patients with Treg deficiency present a broad range of clinical manifestations. A high index of suspicion for a monogenic cause of polyautoimmunity in early childhood can reduce delays in diagnosis. With the increasing availability of targeted therapies, the outcomes of these patients can be significantly improved.